CONTAMINATION BY SESQUITERPENOID DERIVATIVES IN THE ORGUEIL CARBONACEOUS CHONDRITE - Watson J.S.; Pearson V.K.; Gilmour I.; Sephton M.A. (My University, 2003)
The free organic components of the Orgueil carbonaceous chondrite have been the subject of much controversy. Several proposals for their source have been put forward including extraterrestrial abiotic processes, extraterrestrial life and terrestrial contamination. In this study we have analysed the free components to assess their distribution and possible sources. Compounds suggestive of terrestrial contamination by essential plant oil derivatives are evident. Their distribution suggests a source such as cleaning products, disinfectant and air-freshener, where they are present in refined form. This study strongly highlights the need for extreme care when interpreting organic data from meteorites with long curational histories. Future meteorites falls and extraterrestrial sample returns should be stored so as to avoid being compromised by similar terrestrial substances.